Age-induced differences in brain neural activation elicited by visual emotional stimuli: A high-density EEG study. (6th January 2017) - Tsolaki, Anthoula C.; Kosmidou, Vasiliki E.; Kompatsiaris, Ioannis (Yiannis); Papadaniil, Chrysa; Hadjileontiadis, Leontios; Tsolaki, Magda
Highlights: Brain source localization is achieved with high density EEG. Results reveal changes in N170 with aging for two negative emotional stimuli. Differences in brain neural activation at the 'anger' and 'fear' face processing. Higher negativity in the occipito-temporal electrode sites in case of elderly. Aging appears to affect the limbic area neural activation at emotional processing. Abstract: Identifying the brain sources of neural activation during processing of emotional information remains a very challenging task. In this work, we investigated the response to different emotional stimuli and the effect of age on the neuronal activation. Two negative emotion conditions, i.e., 'anger' and 'fear' faces were presented to 22 adult female participants (11 young and 11 elderly) while acquiring high-density electroencephalogram (EEG) data of 256 channels. Brain source localization was utilized to study the modulations in the early N170 event-related-potential component. The results revealed alterations in the amplitude of N170 and the localization of areas with maximum neural activation. Furthermore, age-induced differences are shown in the topographic maps and the neural activation for both emotional stimuli. Overall, aging appeared to affect the limbic area and its implication to emotional processing. These findings can serve as a step toward the understanding of the way the brain functions and evolves with age which is a significant element in the design of assistive environments.